Effect of the stimulative and interactive webpage on library readers’ usage - Nadesan, N.; Thiruchchenthinathan, S. (University of Jaffna, 2022)
The academic libraries play a fundamental role in supporting teaching, learning, and research activities at the University and act as a gateway to knowledge by organizing knowledge products such as books, periodicals, e-resources and other library materials in academic research and creative fields. With the advancement of web technology, most universities have a website for their library, which is instrumental in disseminating and promoting library and library services information to all users. Further, academic library websites provide access to online catalogues, electronic databases, e-resources, past papers, and digital collections to support the research and educational needs of the faculty and student. The study analyzes the role of academic libraries’ stimulative and interactive websites in providing effective services for patrons. This study targets to find out the techniques and practices to proactively maintain a library website for the betterment of knowledge dissemination in academic libraries. Quantitative data collection tools were used to collect data from the academic library patrons. Structured questionnaires were distributed via Google Form, and the data collected from 140 respondents were analyzed using descriptive statistical techniques. All the respondents are members of the academic library at the University level in Sri Lanka. The study found that the patrons with 59.3% encounter problems identifying the books’ physical location at the library. Further, the study found that the patrons’ visits and circulation of books depend on the ease of accessibility to the physical location of the books. 77.9% of patrons expect quick links to access the book by displaying the book’s cover page or content page. Many academic libraries do not have a tool to organize reader communication to help or respond to library users more quickly and effectively. 87.1% of the respondents have pointed out that the website of the academic library in which they are the members does not have any mechanism for quick and effective responses to the patrons’ queries. Therefore, this study recommends that library websites must facilitate adequate information through stimulative and responsive design.
Keywords: Stimulative and interactive website; Academic library; Library clients